2011
DOI: 10.1093/brain/awr195
|View full text |Cite
|
Sign up to set email alerts
|

Motor Neuron dysfunction in frontotemporal dementia

Abstract: Frontotemporal dementia and motor neuron disease share clinical, genetic and pathological characteristics. Motor neuron disease develops in a proportion of patients with frontotemporal dementia, but the incidence, severity and functional significance of motor system dysfunction in patients with frontotemporal dementia has not been determined. Neurophysiological biomarkers have been developed to document motor system dysfunction including: short-interval intracortical inhibition, a marker of corticospinal motor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
201
1
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 288 publications
(217 citation statements)
references
References 69 publications
10
201
1
5
Order By: Relevance
“…In addition, muscle strength of bilateral upper and lower limb muscle groups (deltoid, biceps, wrist extensors, finger flexors, finger extensors, finger abductors, hip flexors, quadriceps, tibialis anterior, and extensor hallucis longus) was assessed using the Medical Research Council scoring system and incorporated into an expanded Medical Research Council sum score (EMRCSS) developed for the detection of muscle weakness in patients with amyotrophic lateral sclerosis (ALS), with a total score of 100. 9 Laboratory investigations were performed to exclude other treatable causes of weakness including primary muscle disease, infection, vasculitis, systemic autoimmune disease, and malignancy. Anti-ganglioside M1 (GM1) antibodies and CSF were not routinely tested because they have not been shown to predict response to IVIg treatment.…”
Section: Methodsology and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, muscle strength of bilateral upper and lower limb muscle groups (deltoid, biceps, wrist extensors, finger flexors, finger extensors, finger abductors, hip flexors, quadriceps, tibialis anterior, and extensor hallucis longus) was assessed using the Medical Research Council scoring system and incorporated into an expanded Medical Research Council sum score (EMRCSS) developed for the detection of muscle weakness in patients with amyotrophic lateral sclerosis (ALS), with a total score of 100. 9 Laboratory investigations were performed to exclude other treatable causes of weakness including primary muscle disease, infection, vasculitis, systemic autoimmune disease, and malignancy. Anti-ganglioside M1 (GM1) antibodies and CSF were not routinely tested because they have not been shown to predict response to IVIg treatment.…”
Section: Methodsology and Treatmentmentioning
confidence: 99%
“…IVIg treatment was continued in the remaining patients and only subsequently ceased when there was definite evidence of disease progression (8 patients, mean IVIg courses 9.9 6 1.8, range [4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Irrespective of subsequent treatment, each patient was then followed in a specialized neuromuscular clinic for an average of 32.6 6 5.0 months from symptom onset (range 8-108 months), and the duration of follow-up for responders after initiation of treatment was a minimum of 12 months.…”
Section: Methodsology and Treatmentmentioning
confidence: 99%
“…Considerable clinical (1,2), genetic (3), pathological (4), and neuropsychological data (2-5) have demonstrated that ALS and frontotemporal dementia (FTD) significantly overlap. The observed cognitive and behavioural changes in ALS parallel those observed in frontotemporal dementia, namely, deficits in executive functions, language functions, verbal fluency, and social cognition (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Since the realisation of clinical, [1][2][3] pathological, 4,5 and genetic [6][7][8][9] overlaps between amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD), studies have increasingly focussed on cognitive deficits in patients with ALS and ALS-FTD. Behavioural changes, similar to those identified in the behavioural variant of FTD, 1,10,11 and executive deficits have been well described, 12 although non-executive cognitive impairment, including language dysfunction, also occurs.…”
Section: Introductionmentioning
confidence: 99%